Evaluation of healthcare science student learning styles based VARK analysis technique - Izdihar Kamal; Muhammad Khalis Abdul Karim; Mohd Mustafa Awang Kechik; Xinni Ni; Hairil Rashmizal Abdul Razak (Institute of Advanced Engineering and Science, 2021)
This study aimed to evaluate the learning styles among healthcare students and to study the relationship with their academic achievement. This cross-sectional study was conducted among 137 healthcare students from six different courses. Data was collected using a self-administered questionnaire and developed based on the original visual, aural/auditory, read/write, and kinesthetic (VARK) assessment. The questionnaire was divided into two sections: the demographic status and the learning style perspective. A total of 119 respondents (86.8%) has chosen unimodal as their learning styles, while the rest of the 18 respondents (13.2%) choose multimodal as their preferred learning method. Among the unimodal learning styles, visual (32%) and reading (26%) were most preferred among respondents. The auditory and kinesthetic methods of learning were less and accounted for 10% to 20%. Notably, in multimodal learning styles preferences, 4% of students prefer a combination learning style of visual and kinesthetic methods. There was no significant relationship between learning styles and academic achievement using Pearson’s Chi-square test (p>0.05). Hence, both were independent of one another. Hence, some of the dominant learning styles needed to be considered based on their future profession.